Parallel Diffractive Multi‐Beam Pulsed‐Laser Ablation in Liquids Toward Cost‐Effective Gram Per Hour Nanoparticle Productivity - Inna Y. Khairani; Maximilian Spellauge; Farbod Riahi; Heinz P. Huber; Bilal Gökce; Carlos Doñate‐Buendía (Advanced Photonics Research, 2024)
Nanoparticles (NPs) generated by pulsed‐laser ablation in liquids (PLAL) have benefited many key applications due to their versatility, enlarged surface area, and high purity. However, scaling up NPs production represents one of the main requisites to commercialize this technology. The established upscaling strategy demands high power and repetition rate laser source with fast scanning systems, which are not widely available and costly. Herein, a cost‐effective alternative is proposed, the addition of static diffractive optical elements to achieve parallel processing through the multi‐beam PLAL (MB‐PLAL). In MB‐PLAL, the optimum repetition rate is reduced to compensate laser energy splitting, hence achieving a higher interpulse distance, reducing pulse shielding, and increasing NPs productivity. MB‐PLAL with 11 beams reached a factor 4 productivity increase for iron–nickel alloy (Fe50Ni50) NPs compared to the single‐beam setup (0.4–1.6 g h−1), and a factor 3 increase for gold (Au) NPs (0.32–0.94 g h−1). The scalability of the proposed MB‐PLAL technique setup is confirmed by Au and Fe50Ni50 NPs productivity experiments using 1, 6, and 11 beams, showing a linear increase in productivity.